Methods for assessing information needs of clinicians in ambulatory care. - Tang, P. C. (American Medical Informatics Association, 1995)
Clinical information systems that provide physicians with relevant information at the time and place where decisions are being made can positively affect the quality and cost of health care. We have developed an assessment methodology to study clinicians' information needs in the context of the work flow and operational constraints of the ambulatory care practice environment. We employed a combination of methods, including observational studies, process flowcharting, semi-structured interviews, and surveys to comprehensively define clinicians' needs. Results from our study point to functional requirements not commonly found in hospital-based systems, such as access to problem lists and medications, computer-based support for health-care team communications, and patient-specific instructions and education.